Rate-Based End-to End Closed Loop Control for ABR Traffic Management - Elvina Djalal (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2017)
ATM has one common feature which guarantees its success, namely the possibility to transport any ATM service, irrespective of its characteristics such as the bit rate, its quality requirements or its bursty nature. ATM also has high flexibility in allocate the bandwidth, and thus allows more calls to enter the network. Unfortunately, this advantage has a negative consequences. ATM presents congestion problems in the network as well as in the end terminals. This research describes about congestion control mechanism that will be applied for Available Bit Rate (ABR) Service in ATM networks, namely, the Rate-Based Congestion Control Scheme. This method supports end-to-end closed-loop control and has been indentified as the most appropriate for the support of this service by ATM Forum. ABR Service is a new ATM Service category. This kind of service automatically and dynamically allocates the available bandwidth to users by controlling the traffic flow based on feedback information. The source increases or decreases the source rate of cells transmission based on the information in the feedback Resource Management (RM) cell it receives. This method minimizes the duties of intermediate nodes and the destination node, so it is expected the source will receive the feedback information faster.